WORK DISCIPLINE AND MOTIVATION: THEIR IMPACT ON EMPLOYEE PERFORMANCE AT THE REGIONAL OFFICE OF THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE, SOUTH SULAWESI - Ahmad, Ibrahim (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study aims to examine the significant impact of work discipline on employee performance, analyze the influence of motivation on performance, and evaluate the combined influence of work discipline and motivation on employee performance at the Regional Office of the Directorate General of Customs and Excise, South Sulawesi. The research was conducted at the Regional Office with 93 respondents (full sampling). Data were described descriptively, and quantitative data analysis was performed using Multiple Linear Regression. The results indicate that discipline plays a positive and significant role in enhancing employee performance. This discipline is reflected in compliance with work rules, effective time management, creation of a conducive work environment, and timely task completion. However, employee motivation does not significantly affect their performance. Motivational factors such as the nature of the work itself, lack of recognition, low morale, job responsibility, and compensation do not contribute significantly to employee performance. Collectively, work discipline and motivation have a positive and significant influence on employee performance. Improved employee performance in terms of quantity, quality, work standards, knowledge, and creativity is influenced by the level of work discipline and motivation in carrying out tasks at the Regional Office of the Directorate General of Customs and Excise, South Sulawesi. These findings provide valuable insights for management in developing strategies that support productivity and employee performance in similar organizations.